Parameter estimation of a DC-DC converter using an extended Kalman filter for fault detection - Zhang, Chen (2014)
DC/DC converters are used frequently in the power supply system of a satellite. Its reliability and maintainability is very important, therefore, the early stage diagnosis of potential parameter failure is very important for reducing stopping time, predictive maintenance and fault-tolerant system. In this project, the objective was to build a DC-DC Buck converter for fulfilling the requirements of parameter estimation using Kalman filter. To prevent the EMI noise affects sampling the desired signal, efforts were made to undo the EMI noise, such as adding a snubber circuit, adding a EMI filter. Other additional components were also added to improve the output voltage. A digital feedback control was incorporated to the Buck converter by using a MCU. The program design was introduced. Another Buck converter as a backup converter which is the same as the first one was built for replacement as the failure was detected in the first one. Finally, a hot-swap circuit was added to the circuits for preventing the inrush current while the backup Buck converter was first time to connect.